Achieving Rigor in Literature Reviews: Insights from Qualitative Data Analysis and Tool-Support - Bandara, Wasana; Furtmueller, Elfi; Gorbacheva, Elena; Miskon, Suraya; Beekhuyzen, Jenine (Communications of the Association for Information Systems, 2015)
It is important for researchers to efficiently conduct quality literature studies. Hence, a structured and efficient approach is essential. We overview work that has demonstrated the potential for using software tools in literature reviews. We highlight the untapped opportunities in using an end-to-end tool-supported literature review methodology. Qualitative data-analysis tools such as NVivo are immensely useful as a means to analyze, synthesize, and write up literature reviews. In this paper, we describe how to organize and prepare papers for analysis and provide detailed guidelines for actually coding and analyzing papers, including detailed illustrative strategies to effectively write up and present the results. We present a detailed case study as an illustrative example of the proposed approach put into practice. We discuss the means, value, and also pitfalls of applying tool-supported literature review approaches. We contribute to the literature by proposing a four-phased tool-supported methodology that serves as best practice in conducting literature reviews in IS. By viewing the literature review process as a qualitative study and treating the literature as the “data set”, we address the complex puzzle of how best to extract relevant literature and justify its scope, relevance, and quality. We provide systematic guidelines for novice IS researchers seeking to conduct a robust literature review.